Islamic Ecoteology, Environmental Tafsir, and Fiqh Al-Bi'ah: Rethinking Islamic Sustainability in Indonesia's Climate Crisis (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
This article examines the intersection of Islamic ecoteology, environmental Quranic interpretation (tafsir al-bi'ah), and the jurisprudence of the environment (fiqh al-bi'ah) within the context of Indonesia's accelerating climate crisis. Drawing on classical Islamic sources, contemporary ecotheological scholarship, and Indonesian Islamic legal discourse, the study argues that Islamic teaching provides a robust normative framework for ecological sustainability one rooted in the Quranic concepts of khalifah (stewardship), amanah (divine trust), and mizan (cosmic balance). The research employs a qualitative library-based methodology combining textual analysis of Quranic verses and hadith with a review of classical and contemporary fiqh literature. Findings reveal three interlocking dimensions: (1) a theological mandate for environmental stewardship embedded in Quranic ontology; (2) a jurisprudential tradition capable of generating binding environmental norms through fiqh al-bi'ah; and (3) significant, yet underexplored, potential for Indonesian Muslim institutions particularly pesantren networks and Majelis Ulama Indonesia to operationalize Islamic sustainability principles in response to climate breakdown. The article concludes that ecoteology and fiqh al-bi'ah must be integrated into mainstream Islamic education and fatwa practice in Indonesia to translate theological imperatives into meaningful environmental governance.
Keywords: Islamic ecoteology; environmental tafsir; fiqh al-bi'ah; climate crisis; Islamic sustainability; Indonesia